AKAPs-PKA disruptors increase AQP2 activity independently of vasopressin in a model of nephrogenic diabetes insipidus - Fumiaki Ando (Nature Portfolio, 2018)
Patients suffering from congenital nephrogenic diabetes insipidus (NDI) fail to concentrate urine due to mutations in vasopressin type 2 receptor (V2R). Here Ando et al. show that agents disrupting the interaction between PKA and AKAPs restore aquaporin-2 activity downstream of V2R, offering a therapeutic approach for the treatment of NDI.